Differences in the Incidence of Gestational Diabetes between Women of Turkish and German Origin: An Analysis of Health Insurance Data From a Statutory Health Insurance in Berlin, Germany (AOK), 2005–2007 - Reeske, A.; Zeeb, H.; Razum, O.; Spallek, J. (Geburtshilfe und Frauenheilkunde, 2012)
Background: Gestational diabetes increases the risk of maternal and infant complications and long-term health effects. A study of differences in the incidence of gestational diabetes between women of Turkish and German origin can identify high risk groups and may indicate the need for culturally sensitive diabetes information and treatment during pregnancy. Method: We analysed all pregnancy related health insurance data from the AOK Berlin (a statutory health insurance in Berlin) based on data from 2005 to 2007, using a name algorithm to identify cases with Turkish migrant background. A group of German women insured with the AOK Berlin served as a comparison group. Results: After exclusion of miscarriages and multiple births the data set comprised 3338 pregnancies in total. The incidence of gestational diabetes was significantly higher in women of Turkish origin with 183 per 1000 pregnancies than in German women (138 per 1000 pregnancies). Regression analyses showed that women of Turkish origin with obesity were at the highest risk of gestational diabetes (OR = 2.67; 95 % confidence interval 1.97–3.60). Conclusion: Obesity is an important factor in explaining the higher incidence of gestational diabetes in women of Turkish origin, especially among young Turkish women. These findings should stimulate discussion as to whether or not information about risk factors such as diabetes within the scope of prenatal care adequately addresses the needs of migrant women. Further research is needed to identify potential differences in undetected and primarily in insufficiently treated gestational diabetes between Turkish and German women.
Keywords: migration and health; Turkey; pregnancy; perinatal health; gestational diabetes